Finding a Needle in a Haystack: The Diagnosis of a Rectal Neuroendocrine Tumor by Transrectal Prostate Biopsy - Coelho,Rosa (2015)
Introduction: Prostate biopsy, usually performed by a transrectal approach, is executed when there is a suspicion of prostate cancer. Neuroendocrine tumors (NETs) are epithelial neoplasms with predominant neuroendocrine differentiation and only 19% of them are localized in the rectum. Case report: The authors describe a 73-year-old man without a significant past medical history that underwent a prostate biopsy because of urinary complaints and elevated serum levels of prostate specific antigen. The histology revealed a well-differentiated NET characterized as a low-grade tumor (G1). A total colonoscopy revealed a 5mm sessile rectal polyp and in the splenic flexure a sessile lesion with central ulceration with 5 cm with histological features compatible with an adenocarcinoma. Conclusion: This is the first case reported in the literature of a rectal NET diagnosed by transrectal prostate biopsy. This case is particularly unique because the diagnosis of the NET lead to the subsequent timely detection of a colonic adenocarcinoma.